Eating habits and nutritional status of pregnant women and the course and outcomes of pregnancy - Suliga, Edyta (Medical Studies/Studia Medyczne, 2015)
The eating habits and nutritional status of future mothers have an important effect, not only on the course of pregnancy and the development of the foetus, but also on the health of the children during subsequent years of life. The objective of the study was the analysis of the relationship between eating habits and nutritional status of pregnant women on the course of pregnancy and pregnancy outcomes, based on a literature review. In the presented study the following are discussed: nutritional risk factors of pre-term birth, gestational diabetes, preeclampsia, low birth weight, infants born small for gestational age, as well as macrosomia and babies born large for gestational age. In the analysis, data was used concerning the consumption of individual products, groups of products, and dietary patterns, without consideration of dietary supplementation.